Impact of sleep deprivation testing on the character of bioelectrical brain activity at patients with temporal lobe epilepsy in interattack period - N. A. Lobanova; L. V. Kapilevich; V. M. Alifirova; O. V. Grebenyuk; T. V. Bayusova; Ye. Yu. Lapina (Бюллетень сибирской медицины)
42 patients with verified diagnosis «temporal lobe epilepsy* have been examined with the aim of investigation of 24-hours sleep deprivation (SD) impact on bioelectrical brain activity at patients with partial epilepsy by electroencephalography method.It has been found that bioelectrical brain activity at patients with temporal lobe epilepsy was characterized by the prevalence of slow activity of greater range as compared to the indices of healthy people, and by significant range skewness. Under the im¬pact of testing with 24-hours SD at epilepsy patients it has been registered the decrease of slow rate range while at healthy people it has been registered the increase of the range and of the indices ofot-rate as well as of slow waves.Using of testing with 24-hours SD increases the efficiency of hidden form paroxysmal activity diagnostics by 2 times.